Defining the Mechanistic Correlates of Protection Conferred by Whole-Cell Vaccination against Pseudomonas aeruginosa Acute Murine Pneumonia - Sen-Kilic, Emel (Infect Immun, 2021)
Pseudomonas aeruginosa is a Gram-negative pathogen that causes severe pulmonary infections associated with high morbidity and mortality in immunocompromised patients. The development of a vaccine against P. aeruginosa could help prevent infections caused by this highly antibiotic-resistant microorganism. We propose that identifying the vaccine-induced correlates of protection against P. aeruginosa will facilitate the development of a vaccine against this pathogen. In this study, we investigated the mechanistic correlates of protection of a curdlan-adjuvanted P. aeruginosa whole-cell vaccine (WCV) delivered intranasally. The WCV significantly decreased bacterial loads in the respiratory tract after intranasal P. aeruginosa challenge and raised antigen-specific antibody titers. To study the role of B and T cells during vaccination, anti-CD4, -CD8, and -CD20 depletions were performed prior to WCV vaccination and boosting. The depletion of CD4(+), CD8(+), or CD20(+) cells had no impact on the bacterial burden in mock-vaccinated animals. However, depletion of CD20(+) B cells, but not CD8(+) or CD4(+) T cells, led to the loss of vaccine-mediated bacterial clearance. Also, passive immunization with serum from WCV group mice alone protected naive mice against P. aeruginosa, supporting the role of antibodies in clearing P. aeruginosa. We observed that in the absence of T cell-dependent antibody production, mice vaccinated with the WCV were still able to reduce bacterial loads. Our results collectively highlight the importance of the humoral immune response for protection against P. aeruginosa and suggest that the production of T cell-independent antibodies may be sufficient for bacterial clearance induced by whole-cell P. aeruginosa vaccination.